Document management through the Institutional Archives System. An approach from the Mexican normative order - Sosa del Angel, Carlos Omar; Caballero Rico, Frida Carmina; Guzmán García, Juan Carlos; Perales Garza, Claudia Yadira (Revista General de Información y Documentación, 2022)
A revision of the regulations of the Institutional System of Archives is carried out based on the concept of document management. Therefore, for the revision, the organizational structure is considered, which is composed of five areas: coordination of archives, correspondence, file processing, file concentration and historical archive. For each area, we analyze the principles, guidelines, procedures, and structure, based on the life cycle of documents in terms of use and management of files. This allows the evaluation of the legal certainty in the administrative acts that derive from the documentary administration and compliance regarding transparency, access to information and accountability in Mexico.